Deficiência intelectual e os apoios necessários na ampliação das habilidades para a autonomia - Raskopf, Miriã (2022)
The research in question brings a reflection on intellectual disability and the extra support needed to expand the skills for the autonomy of subjects with intellectual disabilities, it is a Field Research, developed for the conclusion of the Licentiate Degree in Evening Special Education at Federal University of Santa Maria (UFSM), with the participation of adults with intellectual disabilities residing in the city of Santa Maria, RS. The general objective was to analyze the support used and the benefits generated for the development of skills for the subject's autonomy, in order to emphasize the importance of individualized support and resources to enhance the autonomy of the subject with disabilities in the preparation for adult life. . To better understand the theme, we will go through a little of the history of the subject with intellectual disabilities, the social barriers and the struggles for rights within the public policies that marked this trajectory of social exclusion and abandonment, based on prejudices of inability to exercise a profession, to be able to make choices and attend schools, take a vocational or undergraduate course, denying the opportunity and participation of people with disabilities to social spaces that will provide them with learning through socialization, as well as the lack of adequate resources and support can to form gaps in the formation of the conceptual, social and practical adaptive skills set, fundamental for the development of autonomy skills used in any person's adult life.